Amending the Polish Adaptation of the Moral Foundations Questionnaire (MFQ-PL) - Kelley, Leslie; Fanslau, Agnieszka; Kałowski, Piotr (Przegląd Psychologiczny, 2023)
The current article aims at correcting some linguistic inconsistencies between the Polish and English versions of the 30-item Moral Foundations Questionnaire, and to develop a revised Polish translation more appropriate for cross-cultural comparison. Researchers who are not familiar with the Polish language and the English version of the Moral Foundations Questionnaire are likely to miss these inconsistencies between the English and Polish versions. These translation issues are of significant interest as the Moral Foundations Questionnaire has been utilized to compare human values across a wide range of cultures. In cross-cultural research, translational precision is important, as differences of meaning can lead researchers to draw illusory conclusions about differences between cultures. We offer a revised Polish translation of the 30-item Moral Foundations Questionnaire, which we believe more accurately represents the meaning and form of the English items. This new translation should facilitate more consistent comparisons of moral foundations between Polish and Non-Polish populations.